2017
DOI: 10.1039/c7fo00331e
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mechanisms involved in postprandial glycemia and insulinemia attenuation with dietary fibre consumption

Abstract: This work examines the mechanisms involved in the attenuation of postprandial glycemic and insulinemic responses associated with soluble dietary fibre (SDF) consumption. The effect of SDF, including yellow mustard mucilage, soluble flaxseed gum and fenugreek gum on in vitro amylolysis and maltose transport was studied. Furthermore, a human clinical trial was conducted to investigate the effect of SDF consumption on postprandial glycemic and insulinemic responses and gastric emptying, as estimated based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 74 publications
0
24
0
Order By: Relevance
“…Each value represents the mean ± SE (n = 8). # p < 0.05 versus RD; *p < 0.05 versus HFD β-actin plasma (Repin et al, 2017;Villanueva-Suárez, Pérez-Cózar, Mateos-Aparicio, & Redondo-Cuenca, 2016). However, in our previous studies where mice were fed a HFD and HFD mixed with PGBR, although there were no differences in the amount of dietary fibers in those two groups, the mice fed with HFD mixed PGBR were healthier than those fed with HFD only (Shen et al, 2016(Shen et al, , 2015Yen et al, 2017).…”
Section: Discussionmentioning
confidence: 72%
“…Each value represents the mean ± SE (n = 8). # p < 0.05 versus RD; *p < 0.05 versus HFD β-actin plasma (Repin et al, 2017;Villanueva-Suárez, Pérez-Cózar, Mateos-Aparicio, & Redondo-Cuenca, 2016). However, in our previous studies where mice were fed a HFD and HFD mixed with PGBR, although there were no differences in the amount of dietary fibers in those two groups, the mice fed with HFD mixed PGBR were healthier than those fed with HFD only (Shen et al, 2016(Shen et al, , 2015Yen et al, 2017).…”
Section: Discussionmentioning
confidence: 72%
“…Dietary fiber and phenolic compounds are known to induce satiety by different mechanisms. Short‐term satiety is exerted through delayed gastric emptying (mainly by soluble fiber), by altering the viscosity of the alimentary bolus at gastric level . Satiety also occurs by modulating secretion of gastric inhibitory polypeptide and glucagon‐like peptide‐1 (short‐term), as well as leptin (long‐term) .…”
Section: Resultsmentioning
confidence: 99%
“…Short-term satiety is exerted through delayed gastric emptying (mainly by soluble fiber), by altering the viscosity of the alimentary bolus at gastric level. 34 Satiety also occurs by modulating secretion of gastric inhibitory polypeptide and glucagon-like peptide-1 (short-term), 35 as well as leptin (long-term). 36 Modifying the gut-brain axis signals by actions of the gut microbiota is a complementary method that can exert satiety.…”
Section: Bioassay Performancementioning
confidence: 99%
“…Most common explanations usually refer to an unmediated ability of soluble fiber to delay glucose absorption [ 74 ]. However, Repin et al recently found that multiple types and doses of soluble fiber are able to induce similar reductions in postprandial glycemia and insulinemia, concluding that a modified meal viscosity and maybe a slower gastric emptying are involved [ 75 ]. Steinert et al reported the use of oat bran mixed in water as a preload before a white bread test meal to efficiently reduce the postprandial glycemic area under curve and speculated it may be correlated to a delayed gastric emptying [ 76 ].…”
Section: Influence Of Nutrients On Gastric Emptying and Glycemic Lmentioning
confidence: 99%